Isolation and characterization of a terpene synthase gene from bangun-bangun [Plectranthus amboinicus (Lour.) spreng.] - Teh, Kah Yee (2019)
Plant natural products play important roles in the pharmaceutical field. Based on World Health Organization, 80% of the world population uses herbal plants as their medications to treat diseases because herbal plants are commonly accessible, effective and considered safer to be consumed by humans. Plectranthus amboinicus or bangun-bangun in Malaysia is a herbal plant and its bioactive compounds like terpenoids contributed to the properties and potential applications in the pharmaceutical field. Plant-derived terpenoids were proven by research and clinical studies to have great potentials for use as medicine and drugs. However, commercialization of plant-derived terpenoids has been challenging as they are present at low amount. This study was aimed to isolate, clone and functionally characterize the transcript of a terpene synthase gene from P. amboinicus. A novel full length transcript sesquiterpene synthase (designated as PamTPS2) was isolated, cloned and identified with an open reading frame of 1653 bp that encoded a 551 amino acids protein. The molecular weight of the deduced protein was approximately 64 kDa with an isoelectric point (pI) value of 5.68. Conserved motifs that are typically present in terpene synthases were also found in deduced PamTPS2 protein. The conserved motifs found were aspartate-rich DDXXD motif that is critical for positioning substrates, a NSE/DTE motif that can fix pyrophosphate substrate, and a RXR motif involving in the complexation of the diphosphate group after substrate ionization. Thus, it was suggested that PamTPS2 belongs to class I terpene synthase and of the TPS-b group. Besides, the 3-D protein structure of PamTPS2 was constructed using SWISS-MODEL and MODELLER 9.21 and validated via in silico analysis. It was revealed that the 3D structure ofPamTPS2 was made up of 34 α-helices, 2 β-sheets and 34 turns. Through molecular docking, it was further revealed that PamTPS2 could be a multi-substrate enzyme as it has affinity towards three potential substrates in the following order (highest to lowest), which are, farnesyl pyrophosphate, geranyl pyrophosphate and geranylgeranyl pyrophosphate. Real-time quantitative polymerase chain reaction (RT-qPCR) was performed on leaf and stems at three different timepoints 8AM, 2PM and 8PM. PamTPS2 transcript was shown to be expressed 5 folds higher in the leaf than the stems at 8AM. However, at 2PM, it was expressed around 140 folds higher in stem than leaves. The PamTPS2 cDNA was cloned into pMAL-c5x vector and expressed in Escherichia coli BL21 strain. Functional enzymatic assays were performed to analyze the potential products produced from the catalytic activity of PamTPS2. Based on in vivo enzymatic test on E. coli habouring pMAL-c5x:PamTPS2, caryophyllene and β-sesquiphellandrene were produced as final products. However, in vitro enzymatic tested on purified PamTPS2 did not show any targeted terpene products. The successful isolation of a novel functional sesquiterpene synthase from P. amboinicus would be beneficial to be applied in the pharmaceutical field.